The Derveni papyrus: cosmology, theology, and interpretation - Betegh, Gábor (Cambridge University Press, 2004)
This is a comprehensive study of the Derveni Papyrus. The papyrus, found in 1962 near Thessaloniki, is not only one of the oldest surviving Greek papyri but is also considered by scholars as a document of primary importance for a better understanding of the religious and philosophical developments in the fifth and fourth centuries BC. Gábor Betegh aims to reconstruct and systematically analyse the different strata of the text and their interrelation by exploring the archaeological context; the interpretation of rituals in the first columns of the text; the Orphic poem commented on by the author of the papyrus; and the cosmological and theological doctrines which emerge from the Derveni author's exegesis of the poem. Betegh discusses the place of the text in the context of late Presocratic philosophy and offers an important preliminary edition of the text of the papyrus with critical apparatus and English translation.